Systematic pattern analyses of Vδ2+ TCRs reveal that shared “public” Vδ2+ γδ T cell clones are a consequence of rearrangement bias and a higher expansion status - Deng, Lihua; Harms, Anna; Ravens, Sarina; Prinz, Immo; Tan, Likai (Frontiers in Immunology, 2022)
Background: Vγ9Vδ2+ T cells are a major innate T cell subset in human peripheral blood. Their Vδ2+ VDJ-rearrangements are short and simple in the fetal thymus and gradually increase in diversity and CDR3 length along with development. So-called "public" versions of Vδ2+ TCRs are shared among individuals of all ages. However, it is unclear whether such frequently occurring "public" Vγ9Vδ2+ T cell clones are derived from the fetal thymus and whether they are fitter to proliferate and persist than infrequent "private" clones. Methods: Shared "public" Vδ2+ TCRs were identified from Vδ2+ TCR-repertoires collected from 89 individuals, including newborns (cord blood), infants, and adults (peripheral blood). Distance matrices of Vδ2+ CDR3 were generated by TCRdist3 and then embedded into UMAP for visualizing the heterogeneity of Vδ2+ TCRs. Results: Vδ2+ CDR3 distance matrix embedded by UMAP revealed that the heterogeneity of Vδ2+ TCRs is primarily determined by the J-usage and CDR3aa length, while age or publicity-specific motifs were not found. The most prevalent public Vδ2+ TCRs showed germline-like rearrangement with low N-insertions. However, age-related features were also identified. Public Vδ2+ TRDJ1 TCRs from cord blood showed higher N-insertions and longer CDR3 lengths. Synonymous codons resulting from VDJ rearrangement also contribute to the generation of public Vδ2+ TCRs, that one public TCR was always produced by multiple different transcripts and even with different D gene usage. Furthermore, the publicity of Vδ2+ TCRs is positively associated with expansion status. Conclusion: We conclude that the heterogeneity of Vδ2+ TCRs is mainly determined by TRDJ-usage and length of CDR3 aa sequence. Public Vδ2+ TCRs result from germline-like rearrangement and synonymous codons. Public Vδ2+ TCRs associated with higher expansion status suggest they have an advantage in expansion.